Effect of Temperature on Rates of Alternative and Cytochrome Pathway Respiration and Their Relationship with the Redox Poise of the Quinone Pool - Atkin, Owen K. (American Society of Plant Physiologists, 2002)
We investigated the effect of short-term changes in temperature on alternative (Alt) and cytochrome (Cyt) pathway respiration, both in intact tissues and isolated mitochondria of 14-d-old cotyledons of soybean (Glycine max L. cv Stevens). We also established the extent to which temperature alters the interaction between the oxidizing pathways and the level of ubiquinone (UQ) reduction (UQ(r)/UQ(t)). No difference was found between the temperature coefficient of respiration (Q(10); proportional change per 10°C) of Alt and Cyt pathway respiration in cotyledon slices (Q(10) = 1.92 and 1.86, respectively). In isolated mitochondria, the Q(10) of the fully activated Alt pathway (Q(10) = 2.24–2.61) was always equal to, or higher than, that of Cyt c oxidase (COX) alone (Q(10) = 2.08) and the complete Cyt pathway (Q(10) = 2.40–2.55). This was true regardless of substrate or whether ADP was present. There was little difference in the Q(10) of the Cyt pathway with or without ADP; however, the Q(10) of COX was substantially lower in the presence of an uncoupler (Q(10) = 1.61) than its absence (Q(10) = 2.08). The kinetics of Alt and Cyt pathway activity in relation to UQ(r)/UQ(t) were not affected by temperature. For a given UQ(r)/UQ(t) value, the proportion of maximum flux taking place was similar at all temperatures for both pathways (±ADP). However, the Q(10) of the Alt and the Cyt pathways (+ADP) increased with increasing UQ(r)/UQ(t). We conclude that the Alt pathway is not less temperature sensitive than the Cyt pathway or COX per se and that changes in the degree of control exerted by individual steps in the respiratory apparatus could result in changes in the Q(10) of mitochondrial O(2) uptake.